Trashumancia, Espacio para Poesía y Arte : N° 16 - Ocaranza, Jorge Octavio (dirección); Gutiérrez Ramírez, Alfredo (edición) (Trashumancia, 1993)
Contiene obra de: Lauro Zavala, José Brú, César López Cuadras, Carlos E. Bustos, Federico Pérez, José Tarim, Efrén Rodríguez, José Luis Silva, Leticia Vallejo, Octavio Romero, Rafael Mesina, Verónica Zamora, Víctor Manuel Cárdenas, Rubén Alcántar, Hugo Hiriart, Valerio Magrelli, Alejandro Zapa, Alicia Zúñiga Llamas, Arnulfo Sepúveda, Felipe Ponce, Francisco Javier Ibarra, Hugo Medrano, Jesús Díaz, Katia Castañeda, León Plascencia Ñol, Luis Armenta Malpica, María Esther de la Garza, María Teresa Gutiérrez, Miguel Cruz Robles, Teresa Blanco, Jorge Octavio Ocaranza y José Guadalupe Ramírez.